Matrix Stiffness Induces Midnolin-dependent Lamin B1 Degradation to Control Myoblast Differentiation - Guo, Liping; Zhao, Yanjing; Zhang, Zhe; Sun, Chang; Xie, Yafan; Dai, Qin; Yan, Yan; Zhou, Yaoqi; Zhang, Yang; Li, Quhuan; Qiu, Juhui; Peng, Qin (LangTaoSha Preprint Server, 2025)
Cells decode mechanical cues to direct fate decisions through nuclear remodeling, yet nuclear adaptors to mechanical signals remain elusive. Here, we show that soft matrix suppresses myoblast differentiation and induces nuclear abnormality within 30 minutes, accompanied by a >60% reduction in lamin B1 proteins levels. Mechanistically, midnolin interacts with lamin B1 and mediates ubiquitination-independent degradation of lamin B1 on soft matrix, through the Catch domain of midnolin engaging a b-strand within lamin B1’s Ig-like domain. Functionally, moderate lamin B1 expression is essential for myoblast differentiation initiation, as its depletion either by siRNA or CRISPR knockout abolishes myogenic capacity. Our findings reveal that the midnolin-proteasome axis directly converts mechanical inputs into lineage commitment by triggering lamin B1 degradation, defining a novel nuclear mechano-adaptation pathway.